Improved cholera control in Kenya: A retrospective analysis of 2017–2019 in Nairobi and Homabay - Kyeng Mercy; Ganesh Pokhariyal; Noah T. Fongwen; Nicaise Ndembi; Lucy Kivuti-Bitok (Journal of Public Health in Africa)
Background: Kenya has recorded at least 38 678 cases and 695 deaths over the last decade, and costing on average $2.2 million annually. From 2014 to 2016, the country experienced one of the deadliest and largest outbreak. However, between 2017 and 2020, there was a decline in the number of reported cases and deaths.